Resistance to pesticin, storage of iron, and invasion of HeLa cells by Yersiniae. - Sikkema, D J (1987)
The independent abilities of Yersinia pestis to absorb exogenous pigments including hemin and Congo red (Pgm+) and to produce the bacteriocin pesticin with genetically linked invasive enzymes (Pst+) are established virulence factors of the species. Pst- Pgm+ strains of Y. pestis are sensitive to pesticin (Psts), and mutation of these isolates to pesticin resistance (Pstr) is known to result in concomitant conversion to Pgm-. Wild-type cells of Yersinia pseudotuberculosis and Yersinia enterocolitica are Pgm- but may be Psts; mutation of the latter to Pstr also results in avirulence. In this study, typical Pgm- mutants of Y. pestis exhibited a dramatic nutritional requirement at 37 degrees C but not 26 degrees C for iron which could be fulfilled by either Fe3+ or hemin. Iron privation of Pgm- yersiniae resulted in formation of osmotically stable spheroplasts similar to those previously observed after exposure of Psts bacteria to pesticin. At 37 degrees C, Pgm+ organisms rapidly overgrew initially predominant Pgm- populations in iron-deficient medium. However, Pgm-isolates could undergo a second mutation that permitted successful competition with Pgm+ cells in this environment. The mutation to Pstr in Y. pseudotuberculosis and Y. enterocolitica did not promote a similar requirement for iron but rather prevented these organisms from penetrating HeLa cells. The ability to invade these nonprofessional phagocytes was not shared by Pgm+ or Pgm- cells of Y. pestis.